2018
DOI: 10.1177/2167696817752950
|View full text |Cite
|
Sign up to set email alerts
|

Coping and Resilience in the Transition to Adulthood

Abstract: Three general types of coping (problem-focused coping, social support-seeking, and meaning-focused coping) in the transition from adolescence to early adulthood are examined. Specifically, we investigated age differences, their interdependence, and their adaptive function in respect to academic work-related stress (resilience). The present study examined these issues in a crosssectional assessment (1,608 pupils and students between 14 and 30 years). Problem-focused coping and seeking social support were positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 48 publications
(84 reference statements)
2
44
0
2
Order By: Relevance
“…Along the same lines, studies in the field of school psychology support the development of social and emotional skills that contribute to the positive adjustment and mental well-being of adolescents, such as mental resilience, which appears to reduce the negative effects of stress [10,11]. The term "mental resilience" refers to a dynamic process in which a person exhibits positive adaptation or ability to maintain and regain his mental health and balance during challenging and adverse conditions, using one's own abilities and available support systems [12].…”
Section: Introductionmentioning
confidence: 97%
“…Along the same lines, studies in the field of school psychology support the development of social and emotional skills that contribute to the positive adjustment and mental well-being of adolescents, such as mental resilience, which appears to reduce the negative effects of stress [10,11]. The term "mental resilience" refers to a dynamic process in which a person exhibits positive adaptation or ability to maintain and regain his mental health and balance during challenging and adverse conditions, using one's own abilities and available support systems [12].…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, recent studies have demonstrated increased levels of emotional distress during the COVID-19 pandemic among young adults (Liang et al, 2020;Liu, Zhang, Wong, Hyun, & Hahm, 2020;Shanahan et al, 2020;Tee et al, 2020;Wang et al, 2020aWang et al, , 2020b. In normal times, young adults embark on a new phase in their lives and make numerous self-defining choices with long-term consequences (Arnett, 2015;Leipold, Munz, & Mich ele-Malkowsky, 2019), such as preparing for the school-to-work transition (Blustein, Juntunen, & Worthington, 2000) and establishing individuality and financial independence (Shulman, Feldman, Blatt, Cohen, & Mahler, 2005). Given these unique developmental challenges, we conducted the present study to better understand unique ways in which young adults psychosocially react to and cope with pandemic-related stressors.…”
mentioning
confidence: 99%
“…Inadequacy of stress coping skills could easily trigger loss of self-control leading to a violent act, which, depending on severity, could cause homicide. Certain coping mechanisms have been shown to be positively associated with age, which means that younger people can be less resilient in the face of stress if they don't possess positive coping mechanisms [16]. Additionally, immigrants may have a unique set of stresses, such as fear of deportation, and challenges that could render them less resilient in the face of stress, such as loss of social support [17].…”
Section: Discussionmentioning
confidence: 99%